Analisis Pengaruh Pemilihan Media, Intensitas Penayangan Media, Daya Tarik Pesan Pada Media Terhadap Brand Awareness Dengan Kualitas Komunikasi Pemasaran Sebagai Variabel Intervening (Studi pada Pikatan Waterpark Temanggung) - Hani, Fieha Alfi; Magnadi, Rizal Hari (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to analyze the influence of marketing communication quality to brand awareness with media choosing, intensity of telecast media, and message appeal in media as independent variable. Pikatan Waterpark as the best tourism object in Temanggung need to improve their marketing communication to build brand awareness to introduce Pikatan Waterpark in Central Java. Population used in this study with criteria known Pikatan Waterpark and take sample non-probability purposive sampling around 100 respondent. Respondents fill in the questionnaires and processed with multiple regression analysis using SPSS software. The result are media choosing, intensity of telecast media, and message appeal in media have positive effect on marketing communication quality. And marketing communication quality have positive effect to brand awareness. From three independent, message appeal in media have biggest effect to marketing communication quality.